Agroecosystems and binding buffer zones. The case of the Parque Luro Natural Reserve (Huellas, 2020)
Natural reserves are important to maintain natural heritage and endangered ecosystems. Therefore, there are specific environmental legislation, economic resource allocation and qualified personnel. In the case of Calden Forest these policies, based on Provincial Law N°2624, are efficient to counteract deforestation and fires but are not efficient enough to reduce the risk and environmental problems associated to the advance of agroecosystems, a process which has increased during the last decade. This is the reason why the area of Parque Luro Natural Reserve represents a situation of imminent risk in relation to the context. The aim of this research is to analyze the environmental changes caused by use of rural soil. The methodology applied consists in analyzing current legislation and the environmental management. It is carried out from a diagnosis based on students’ reports, interviews prepared by the faculty of Biogeography, contributions by the Environment Undersecretariat and production statistics for the reserve adjacent area. This comprehensive analysis, reflected in a problems tree, makes it possible to determine the need for creating a binding buffer zone.
Keywords: protected areas; agro-ecosystems; environmental problems; buffer zones